Development and application of the renewable energy regional optimization utility tool for environmental sustainability: REROUTES. (August 2016) - Hori, Keiko; Matsui, Takanori; Hasuike, Takashi; Fukui, Ken-ichi; Machimura, Takashi
Abstract: To expand the use of renewable energy, it is necessary to optimize energy production at a local level through an appropriate combination of different renewable energy resources. Additionally, the environmental impacts from the use of renewable resources must be considered from different perspectives. Thus, this study aims to develop a decision tool that evaluates and optimizes the renewable energy mix at a regional scale with regard to various environmental impacts. This tool was developed by creating a municipal energy database that includes five renewable energies (solar, wind, small- and medium-scale hydro, geothermal and biomass energy) and six evaluation indicators (proportion of developed renewable energy, economic balance, installed wind power, decrease in CO2 emissions, circulation rate of biomass resource, and impacted ecosystem area). Specifying different constraints in the model allowed investigation of the optimal renewable energy combination in a study area for two different scenarios, with the results highlighting the trade-offs between the scenarios. We also optimized the combination of different renewable energies for every municipality across Japan, while incorporating the natural conditions and varying demand structure. In conclusion, the tool developed in this study could support decision-making regarding the development of renewable energy resources. Highlights: Decision support tool named REROUTES for renewable energy mix at local level. Creating of indicators for evaluating multiple environmental impacts caused by renewable energy. Developing an optimization tool of renewable energy mix considering environmental impacts. Evaluating the behavior and functions of REROUTES by case studies.